Dental adhesives in restorative dentistry: A bibliographical revision (Research, Society and Development, 2025)
Objective: To analyze the literature regarding the main adhesive systems used in restorative dentistry, emphasizing their properties and clinical performance. Methods: This study consists of a narrative literature review based on bibliographic research conducted in Portuguese and English through the databases Google Scholar, SciELO, and PubMed. Results: After selecting articles according to predefined inclusion criteria, it was observed that the continuous development of dental adhesive systems has significantly contributed to the advancement of restorative dentistry. The widespread use of different adhesive systems and their respective application protocols highlights the importance of technique specificity as a key factor for achieving optimal bonding between the restorative material and the dental substrate. Conclusion: Therefore, the proper selection and application of various adhesive systems and techniques are essential for ensuring clinical success in restorative procedures and for maximizing the preservation of healthy tooth structure.